DEVELOPMENT OF INSTRUMENT FOR UNDERSTANDING THE CONCEPT OF WRITING SCIENTIFIC ARTICLES FOR LECTURERS USING THE ADDIE MODEL: EMPIRICAL VALIDITY AND RELIABILITY - Luthfi Ilham Ramdhani; Arianda, Yoga Dwi; Awaluddin Tjalla; Lussy Dwiutami Wahyuni (Indonesian Journal of Educational Development (IJED), 2025)
This study aims to develop an instrument to assess lecturers' conceptual understanding of scientific article writing using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The instrument is designed to evaluate lecturers' comprehension of key aspects of scientific writing, including structure, methodology, publication ethics, and the use of academic language. Adopting a research and development approach, the study involved expert validation and empirical testing with 275 respondents from various regions across Indonesia. The findings indicate that the instrument exhibits high content validity, with an average Scale Content Validity Index (S-CVI/Ave) of 0.968, and robust internal reliability, as evidenced by a Cronbach’s Alpha of 0.852. Item-total correlation analysis confirmed the validity of all items, with Corrected Item-Total Correlation values exceeding 0.3044. The instrument functions both as an evaluative tool for assessing lecturers' scientific writing skills and as a learning resource to enhance their competencies. The study concludes that the instrument is a valid and reliable measure of lecturers' conceptual understanding of scientific article writing. Its implications highlight its potential as a vital resource in training and professional development programs for lecturers in higher education institutions.